Inkjet‐Printed Lenses with Adjustable Contact Angle to Improve the Light Out‐Coupling of Organic Light‐Emitting Diodes. Issue 9 (29th June 2021) - Sachs, Ian; Fuhrmann, Marc; Verboven, Inge; Basak, Indranil; Deferme, Wim; Möbius, Hildegard
Abstract : The enhancement of the out‐coupling efficiency of organic light‐emitting diodes (OLEDs) is still the subject of research and development. Bottom‐emission OLEDs emit light through the glass substrate into air. Due to the difference of the refractive indices between glass and air, a significant amount of light is reflected at the glass–air interface back into the glass because of total internal reflection. One possibility to avoid total internal reflection at the glass–air interface is the use of lenses. Herein, the concept of macrolenses for pixelated OLEDs is presented. For the design of the lenses, the vertical and horizontal dimensions of the OLED have to be considered, and the contact angle of the lens has to be adapted to the geometrical conditions. A process based on inkjet etching and inkjet printing has been developed which now allows the printing of lenses with defined radius and contact angle. Measurements of the luminance show an improved out‐coupling efficiency. Abstract : By modifying the wetting properties of the ink on the substrate, inkjet etching and inkjet printing can be used to print lens reservoirs and lenses with tuneable contact angles for pixelated organic light‐emitting diodes (OLEDs). It is demonstrated that adjusting the contact angle internal total reflection can be avoided thus leading to an increase in the out‐coupling efficiency.